CARICOM customs handbook : guide to multilateral environmental agreements - Paul, Claude (CCS GeorgetownGY, 2013)
Aims to assist officials in understanding the practical aspects of enforcing MEAs as part of their normal duties of law enforcement and regulation of trade activities at ports of entry.